The study of rice hybrids obtained in hybridization of the Turkish and Russian varieties in the Rostov region - P. I. Kostylev; E. V. Krasnova; L. M. Kostyleva (Зерновое хозяйство России, 2018)
Rice productivity in this country is insufficient for the needs of population that shows the importance of the studied problem. Thus, it’s necessary to develop new highly productive varieties. The hybrids of the first generation often reveal heterosis which is a reason for significant transgressions in the further generations. It gives an opportunity to select more productive forms. The purpose of the work is to analyze quantitative traits of the hybrids F1 among the Turkish and Russian varieties and their effect on productivity of kernels per panicle. The method of the analysis is a statistic and genetic analysis, which allow establishing a degree of phenotypic domination of the trait and an effect of true heterosis. The field trials have been carried out to study such traits as ‘plant height’, ‘length of panicle’, ‘number of spikelets per panicle’ number of kernels per panicle’, ‘fertility of spikelets’, ‘length, width and weight of kernels’; to find any combinations with high grain productivity; to analyze correlation of ‘kernels weight per panicle’ with some economically valuable traits. The average heterosis of ‘plant height’(4.2%), ‘length of panicle’(2.1%), ‘number of spikelets (35.3%), ‘number of kernels’(27.3%) and ‘kernels weight per panicle’(27.5%) was positive. The heterosis of ‘fertility of spikelets’, ‘length, width and weight of kernels’ was negative (from -5.3% till -8.6%). Among the components of productivity the increase of ‘number of spikelets and kernels per panicle’ significantly increased ‘kernels weight per panicle’ of the hybrids. There is a definite positive correlation between ‘number of kernels per panicle’ and ‘fertility of spikelets and an average negative correlation between ‘plant height’ and ‘length of panicle’. The hybrids F1 produced larger ‘number of kernels per panicle’ due to the increased ‘number of spikelets per panicle’ and high ‘fertility of spikelets’. The materials of the article can be useful for the improvement of rice productivity.